2018
DOI: 10.1128/jvi.00439-18
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 5 E1A-Mediated Suppression of p53 via FUBP1

Abstract: Far-upstream element (FUSE) binding protein 1 (FUBP1) was originally identified as a regulator of the oncogene via binding to the FUSE within the promoter and activating the expression of the gene. Recent studies have identified FUBP1 as a regulator of transcription, translation, and splicing via its DNA and RNA binding activities. Here we report the identification of FUBP1 as a novel binding partner of E1A. FUBP1 binds directly to E1A via the N terminus (residues 1 to 82) and conserved region 3 (residues 139 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Expression of all genes was normalized to cellular GAPDH and was represented as percentage of the GAPDH transcript. We have previously observed that GAPDH mRNA concentration remains steady in IMR-90 cells infected at a similar MOI for up to 48 hours after infection, therefore GAPDH mRNA was an appropriate reference gene [26]. Initially, the levels of E1A mRNA fluctuated around 0.01% of GAPDH levels, with an increase in mRNA levels occurring at the 6 hour mark (Fig 1).…”
Section: Resultsmentioning
confidence: 85%
“…Expression of all genes was normalized to cellular GAPDH and was represented as percentage of the GAPDH transcript. We have previously observed that GAPDH mRNA concentration remains steady in IMR-90 cells infected at a similar MOI for up to 48 hours after infection, therefore GAPDH mRNA was an appropriate reference gene [26]. Initially, the levels of E1A mRNA fluctuated around 0.01% of GAPDH levels, with an increase in mRNA levels occurring at the 6 hour mark (Fig 1).…”
Section: Resultsmentioning
confidence: 85%
“…During stress condition, FUBP1 binds directly to the DNA binding domain of the tumor suppressor p53 to inhibit its recruitment to target promoters [70][71][72]. Consequently, FUBP1 indirectly prevents the p53 stress response pathway that would block viral replication.…”
Section: Indirect Transcriptional Repression: Example With P53mentioning
confidence: 99%
“…FUBP1 also promotes cancer cell proliferation by the transcriptional repression of cell cycle inhibitors P21, P15 and the activation of the positive cell cycle regulator Cyclin D2 in HCC (Table 2) [8]. FUBP1 is also implicated in the inhibition of p53 tumor suppressive activity during stress condition [70][71][72]. FUBP1 prevents the DNA-binding activity of p53, interfering with the regulation of its target genes including P21.…”
Section: A Inappropriate Expression Of Fubp1 Target Genesmentioning
confidence: 99%
“…IMR-90 cells transfected with miRNA inhibitors were infected with HAdV5 (isolated from patients) at an MOI of 10 in serum-free medium. Virus titers were determined 72 h after infection by plaque assays performed on 293T cells [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%